Microbial Communities in Permafrost, Moraine and Deschampsia antarctica Rhizosphere Soils near Ecology Glacier (King George Island, Maritime Antarctic) - Daniel E. Palma; Alexis Gaete; Dariel López; Andrés E. Marcoleta; Francisco P. Chávez; León A. Bravo; Jacquelinne J. Acuña; Verónica Cambiazo; Milko A. Jorquera (Diversity, 2025)
While the recession of glaciers in the Antarctic is of global concern under climate change, the impact of deglaciation on soil microbiomes is still limited. Here, soil samples were collected from permafrost (P), moraine (M) and Deschampsia antarctica rhizosphere (R) soils near Ecology Glacier (Antarctic), and their soil physicochemical properties and microbial communities (bacteria, archaea and fungi) were characterized. Our analyses showed that there were significant differences in the soil properties and microbial communities between the R samples and the P and M samples. Specifically, amplicon sequencing of 16S rDNA revealed high bacterial richness and diversity in the studied soils, which were dominated mainly by the phyla Proteobacteria, Actinobacteriota and Bacteroidota. In contrast, lower richness and diversity were observed in the archaeal communities, which were dominated by the phyla Chenarchaeota (M and R) and Thermoplasmadota (M). In addition, fungal community analysis revealed a lower richness and diversity (M and R), dominated by the phylum Ascomycota. Our observations are consistent with previous reports describing the relevant changes in soil microbial communities during glacial recession, including fewer microbial groups studied in soils (archaea and fungi). However, further studies are still needed to elucidate the contributions of microbial communities to soil formation and plant colonization in ice-free soils in Antarctica under global climate change.